Investigating the performance of Caribbean commercial banks in their mobilization and use of savings - Tennant, David ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Examines the mobilization and use of savings by commercial banks in five Caribbean countries. Highlights areas in which commercial banks in some countries have exhibited higher standards of performance relative to the others.